Simplified Multimodal Biometric Identification - Abhijit Shete; Kavita Tewari (IAES Indonesian Section, 2014)
Multibiometric systems are expected to be more reliable than unimodal biometric systems for personal identification due to the presence of multiple, fairly independent pieces of evidence e.g. Unique Identification Project